PROGRAM TATA RIAS PENGANTIN SUNDA SIGER DI LKP YUWITA KOTA TASIKMALAYA - Jihaan Fauziyyah Resmana; Siti Nida Hasanah; Hanifa Qurrota Aini; Rayhaan Hanna Aulia Rusada (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
LKP Yuwita in the field of Sundanese siger bridal make-up located in the City of Tasikmalaya. This Course and Training Institute aims to empower people who need competence and expertise in the field of Sunda Siger Bridal Makeup. As a result of the Sunda Siger Bridal Makeup training, participants gain special skills so they can create a business in the Sunda Siger Bridal Makeup field. This study aims to find out whether participants received entrepreneurship opportunity training at the Sunda Siger Bridal Makeup training program using descriptive qualitative research methods. Data collection techniques using observation techniques, interview techniques and shooting techniques. In the results of the research that LKP Yuwita succeeded in creating Human Resources who have competence and research skills, graduates can work or open businesses in the field of bridal makeup.